The Influence of Online Marketing Reviews and Prices on Consumer Decisions to Stay: A Case Study of the Preangar Hotel in Bandung - Mona Karina; Endang Iryani (Ilmu Ekonomi Manajemen dan Akuntansi, 2026)
The digital economy has transformed the way consumers seek information, evaluate options, and make purchasing decisions, particularly in intangible service sectors like hospitality. Online reviews from previous customers have become a highly influential source of information in shaping potential guests' perceptions of value and trust. This study aims to analyze the influence of online hotel marketing and pricing on consumer decisions to stay at the Preanger Hotel in Bandung. The study used a quantitative method with an explanatory approach and a cross-sectional survey design. Data were collected through questionnaires from respondents who had made online reservations in 2025. Data analysis used multiple linear regression. The results showed that online marketing reviews had a positive and significant effect on stay decisions, as did price, which also had a positive and significant effect. Simultaneously, both variables contributed 44.4% to the variation in consumer decisions. These findings confirm that digital reputation and perceived price value are important determinants in the consumer decision-making process in the hotel industry, with online reviews showing a relatively more dominant influence than price.